The discreet charm of the police state The landpolizei and the evolution of public order in Bavaria, 1945--1968 - Canoy, Jose Raymund O. (Bell & Howell Information and Learning Company, 2001)
In this study of policing in Bavaria after 1945, I argue that intrusive and authoritarian police supervision and regulation of daily life played a persistent and surprisingly dynamic role in the rapid emergence of modern, suburbanized, and post-agricultural regional societies in rural central Europe after the wreckage of the mid-twentieth century. I examine how an authoritarian concept of public order rooted in older traditions of Bavarian policing antedating the Nazi period continued to operate during the rehabilitation of traditional rural society between the fall of the Third Reich and the stabilization of a west German consumer democracy in the middle 1950s. Embodied in the revival of an autonomous, self-contained bureaucratic corporate culture within a police leadership elite that coexisted uneasily as a "state within a state" alongside emergent systems of constitutional civilian oversight, this traditional authoritarianism involved the redeployment of police in a host of regulatory activities not directly related to crimefighting. These included such traditional police preoccupations as registration and control of residence, commercial, and social activities in the population, selective assimilation or exclusion of social newcomer groups in the postwar countryside, and police surveillance of suspected radicals and nonconformists, activities of doubtful compatibility with the proclaimed norms of the Allied occupation and the postwar west German democratic-constitutional order. However, the subsequent "deprovincialization" of the Bavarian countryside in the later 1950s and the ensuing wave of suburbanization as the region joined the mainstream of the west German economic miracle made authoritarian policing based on intimate knowledge of isolated local communities increasingly unworkable. This neo-traditional policing approach eventually gave way to more technologized and mobile but also less intrusive and authoritarian forms better suited to the post-agricultural consumer landscape emerging in Bavaria by the end of the Konrad Adenauer era. Ultimately however, the eclipse of the older authoritarian praxis was not a direct result of any shift in the ideology of the police bureaucracy, but rather a technocratic effort to preserve the efficiency of police operations in a changed environment where contact between the broad mass of the non-criminal population and policemen was becoming increasingly rare in daily life.